An Exegetical Study of the Good Samaritan (Luke 10:25–37) as a Model of Caring in Nursing Practice - Nova Lina Langingi; Grace Fresania Kaparang (PT FORMOSA CENDEKIA GLOBAL, 2026)
Caring is widely recognized as the essence of nursing practice and remains central to holistic patient care. Contemporary nursing literature increasingly emphasizes compassion, empathy, and spiritual care as essential dimensions of professional nursing. Within Christian nursing education, biblical narratives may provide foundational insights into caring behaviors and holistic healing. This study explores the Good Samaritan narrative in Luke 10:25–37 as a model of caring relevant to nursing practice. Using qualitative biblical exegesis and thematic content analysis, the study identifies key caring themes embedded within the narrative and relates them to Jean Watson’s Theory of Human Caring. The findings reveal seven major caring themes: compassion, presence, caring action, holistic care, sacrifice, advocacy, and human dignity. These themes demonstrate strong parallels with contemporary nursing caring theory and support the integration of biblical perspectives into holistic nursing education and practice. Also, implementing this model requires nurses’ reflective awareness to bridge the gap between administrative demands and patients’ emotional needs. The study contributes to faith integration scholarship by providing a theological and theoretical framework for understanding caring within Christian nursing. Future research may explore other biblical healing narratives and their relevance to nursing, leadership, ethics, and spiritual care.